Effects of step rate manipulation on joint mechanics during running - Heiderscheidt, B. C.; Chumanov, E. S.; Michalski, M. P.; Wille, C. M.; Ryan, M. B. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The objective of this study was to characterize the biomechanical effects of step rate modification during running on the hip, knee, and ankle joints so as to evaluate a potential strategy to reduce lower extremity loading and risk for injury.